(untitled) (KULT_online, 2012)
Maren Ziese works as museum assistant at the National Museum of Berlin. Against the background of participation theories and the ’relational aesthetic’ by Bourriaud, her dissertation poses the question if and how curators are able to initiate exchange processes between the visitors to create exhibition rooms that function as social places. In order to analyse four contemporary art exhibitions relating to the topic of religion and to disclose their curatorial methods, she develops a criteria catalogue. Therein she uses varied methods, for example interviews with the curators and an exhibition checklist, and invites her readers to think about modified as well as new models of curated presentations.